Methodological panorama of clinical trials for diabetic foot ulcers: a scope review of design, implementation and reporting - Zhang, Shuo; Wang, Yanying; Wang, Ling; Fan, Xuechun; Zhao, Jinyue; Wang, Yanyan; Yu, Jing; Yu, Yongjiang; Shi, Yingjing; Yan, Guanchi; Mi, Jia (Frontiers in Endocrinology, 2025)
BackgroundDiabetic foot ulcer (DFU) reduce the quality of life for diabetes patients and creates a significant economic burden on global healthcare systems. Although there has been recent progress in DFU clinical trials, most existing scoping reviews have primarily focused on nursing or diagnostic methods. This review analyzed the characteristics of current DFU clinical trials and assessed research methods. This review focused on refining trial design and provide evidence-based methods for improving treatment outcomes and prognosis.MethodThe study searched clinical trials registered in ClinicalTrials and Chinese Clinical Trial Registry (ChiCTR) (up to August 1, 2025). In addition, the study searched PubMed for clinical trials that were published from August 1, 2015, to August 1, 2025. Data was extracted and presented in tables.ResultThe study revealed a rapid increase in the number of clinical trials focusing on DFU in recent years. Meanwhile, interventions have grown more varied, with skin transplantation, tissue replacement products, and dressings being widely used in clinical practice. Nonetheless, these studies face challenges, such as low methodological quality, lack of primary care studies, and low follow-up rates.ConclusionThe number of DFU clinical trials has increased, and the intervention strategies have become more varied. However, there is a large variation in the populations, design of the studies, and evaluation of their effectiveness.